2015
DOI: 10.1186/s13104-015-1606-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and antimicrobial susceptibility patterns of Shigella among acute diarrheal outpatients in Mekelle hospital, Northern Ethiopia

Abstract: BackgroundEmergence of increased antimicrobial resistance of Shigella species is a global challenge, particularly in developing countries where increased misuse of antimicrobial agents occurs. There is no published data in the study area on the prevalence and antimicrobial susceptibility patterns of Shigella among acute diarrheal patients. This study was therefore, under taken to fill this gap.MethodsUsing cross sectional study method, stool specimens were collected from 216 patients with acute diarrhea at Mek… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
26
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 18 publications
7
26
6
Order By: Relevance
“…In addition to this, the result of this study was in line with the study conducted in Nepal [ 18 ], Turkey [ 19 ] and Nairobi [ 20 ] where 4.6, 3.2, and 2.5%, respectively. Our study has lower prevalence of Shigella compared to the study conducted in Bahir Dar [ 21 ], Mekelle [ 22 ], Anyigba [ 23 ] and Gaborone [ 24 ] with prevalence of 7.85, 13.3, 21.9 and 21% respectively. In contrast, the study conducted in Nigeria–Benin Teaching Hospital, is lower than our finding (1.4%) [ 25 ].…”
Section: Discussioncontrasting
confidence: 60%
“…In addition to this, the result of this study was in line with the study conducted in Nepal [ 18 ], Turkey [ 19 ] and Nairobi [ 20 ] where 4.6, 3.2, and 2.5%, respectively. Our study has lower prevalence of Shigella compared to the study conducted in Bahir Dar [ 21 ], Mekelle [ 22 ], Anyigba [ 23 ] and Gaborone [ 24 ] with prevalence of 7.85, 13.3, 21.9 and 21% respectively. In contrast, the study conducted in Nigeria–Benin Teaching Hospital, is lower than our finding (1.4%) [ 25 ].…”
Section: Discussioncontrasting
confidence: 60%
“…This may be due to those strains moderately susceptible for tetracycline at a certain corner of the country. Our result also indicated that 52.4% resistance was seen against co-trimoxazole and this was comparable with a study done in Hawassa 56.0% (43), Addis Ababa 45.7% (53) and Mekelle 55.6% (42). Inconstant to our nding higher result reported from Gonder 73.4% (49).…”
Section: Discussionsupporting
confidence: 90%
“…This may be due to widespread resistance strain throughout the countries. Another antibiotic resistance of Shigella spp was seen against tetracycline 71.4% and this was comparable with ndings reported from Harar 70.6% (41), Jimma 63.6% (33) and Mekelle 77.8% (42). The result was slightly lower than the study reported from Butajira 82.4% (45), Gondar 86% (52) & 86% (49), Hawassa 90% (34).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…[18][19][20][21][22][23][24] Similarly, monitoring and surveillance of antimicrobial resistance is not conducted in most lower and middle income countries, but available data do show clinically relevant resistance in many common bacterial pathogens. [25][26][27][28][29][30][31][32][33][34][35] The ACT Consortium (www.actconsortium.org) included several studies that evaluated the potential of rapid diagnostic tests for malaria to improve case management for patients with undifferentiated fever in malaria endemic areas. Data from these studies, conducted in multiple geographical, epidemiological, and health system settings, provide the largest and most varied sample to date to assess whether changes in antimalarial prescribing behaviour are associated with shifts in antibiotic prescrib-ing.…”
Section: What Is Already Known On This Topicmentioning
confidence: 99%